Globalization and work - Williams, Steve; Bradley, Harriet; Devadson, Ranji; Erickson, Mark, 1964- (Cambridge, UK. : Polity, 2013)
'Globalization and Work' challenges conceptions of globalisation as a project orchestrated by governments, multinational companies and international agencies. The authors highlight the importance of integrating a grounded, bottom-up perspective which recognises that globalisation is not just something that happens to working people, thereby revealing the fascinating extent to which workers actively engage in producing globalisation.
Includes bibliographical references(251-280) and index.
Keywords: Labor and globalization